Intracerebroventricular Infusion of Gangliosides Augments the Adult Neural Stem Cell Pool in Mouse Brain - Yutaka Itokazu (ASN Neuro, 2019)
We previously reported that ganglioside GD3 is the predominant species in neural stem cells (NSCs) and reduced postnatal NSC pools are observed in both the subventricular zone and dentate gyrus (DG) of GD3-synthase knockout (GD3S-KO) mouse brains. Specifically, deficiency of GD3 in GD3S-KO animals revealed a dramatic reduction in cellularity in the DG of the hippocampus of the developing mouse brain, resulting in severe behavioral deficits in these animals. To further evaluate the functional role of GD3 in postnatal brain, we performed rescue experiments by intracerebroventricular infusion of ganglioside GD3 in adult GD3S-KO animals and found that it could restore the NSC pools and enhance the NSCs for self-renewal. Furthermore, 5xFAD mouse model was utilized, and GD3 restored NSC numbers and GM1 promoted neuronal differentiation. Our results thus demonstrate that exogenously administered gangliosides are capable to restore the function of postnatal NSCs. Since ganglioside expression profiles are associated not only with normal brain development but also with pathogenic mechanisms of diseases, such as Alzheimer’s disease, we anticipate that the administration of exogenous gangliosides, such as GD3 and GM1, may represent a novel and effective strategy for promoting adult neurogenesis in damaged brain for disease treatment.